The peopling of East Asia : putting together archaeology, linguistics and genetics - Sagart, Laurent; Blench, R.; Sanchez-Mazas, Alicia, 1962- (RoutledgeCurzon, 2005)
One of the most dynamic research areas in the prehistory of East Asian regions is the synthesis of the findings of archaeology, linguistics and genetics. Several countries have only recently opened to field research and highly active local groups have made possible a raft of collaborative studies that would have been impossible even a decade ago. This book presents an overview of the most recent findings in all these fields. It will be of great interest to scholars of all disciplines working on the reconstruction of the East Asian past.